Filosofi Masalah Khilafiyah: Ikhtilaf al-Fuqaha' dalam Perpektif Filsafat Sosial - Abdul Mun'im (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2005)
This study aims to analyze the philosophy of difference of opinion (ikhtilaf) among fiqh scholars (fuqaha) in the perspective of social philosophy. Ikhtilaf in Islamic law is often seen as a source of division, even though it has a positive value in the social and intellectual dynamics of Muslims. This study uses a qualitative method with a descriptive-analytical approach, through a literature review of classical and contemporary works that discuss the ikhtilaf al-fuqaha'. The results show that differences of opinion in fiqh are a necessity that arises from differences in methodology, social context, and understanding of sharia texts. In the perspective of social philosophy, ikhtilaf contributes to enriching Islamic discourse and reflects the principle of plurality in Islamic legal thought. Thus, understanding ikhtilaf as intellectual wealth can strengthen tolerance and harmony in Muslim societies.